Pemanfaatan Media Digital dalam Pembelajaran Agama Islam Mata Pelajaran Fikih pada Madrasah Aliyah Negeri (MAN) 3 Medan - Nur Hasanah; Sapri Sapri (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
In the current digital era, integrating technology into education has become increasingly important for enhancing the quality of learning and student engagement. This study aims to evaluate the utilization of digital media in religious education, specifically in the subject of Fiqh at Madrasah Aliyah Negeri (MAN) 3 Medan. Adopting a descriptive qualitative approach, the study collects data from both primary and secondary sources to provide a comprehensive insight. The results indicate that the use of digital media in Fiqh at MAN 3 Medan has been implemented effectively. The school has provided supportive facilities, such as computer laboratories and adequate internet services, which greatly assist students and teachers in accessing and utilizing digital media for learning. This integration of digital media enhances student interaction and engagement, allowing for a deeper understanding of Fiqh material. Additionally, digital media usage facilitates more engaging and interactive teaching methods. For future research, it is recommended to explore more innovative variables and use this study as a reference for developing digital-based learning strategies in madrasahs.